Improving organisational performance through TQM in an Indian manufacturing industry: an empirical study. (30th September 2022) - Gupta, Pardeep; Gupta, Niharika
The aim of this paper is to signify the TQM implementation methodology adopted by a leading tractors manufacturing industry namely XYZ Ltd. (name changed) of Punjab, India; examine the issues faced by the company prior to TQM; and investigate the effectiveness of its implementation. The industry started implementing TQM in 2008 with a purpose to counter business challenges for the realisation of its vision, i.e., 'To be within top two brands in India'. Noteworthy improvement in terms of quality, cost and delivery has taken place as a result of implementing TQM initiatives in the company. The TQM journey of the company remained highly successful, and as a result its market share increased from 9.1% to 12.6%, tractor manufacturing volume increased by 25.5%, sales volume enhanced from 35, 248 to 67, 483 tractors per annum, profit growth became three times within four years and the customer satisfaction increased by 39.5%.